Family Factors and the Emergence of Suicidal Ideation in Adolescents - Luwis, Imelda; Maria Goretti Adiyanti (G-Couns: Jurnal Bimbingan dan Konseling, 2026)
Suicide remains the second leading cause of death among adolescents globally, with suicidal ideation often being the critical precursor. While family factors are recognized as a significant trigger, the qualitative mechanisms remain underexplored. This multiple-case study employed a qualitative design to investigate the family-related dynamics influencing suicidal ideation in adolescents. Three participants (aged 20–21) from Salatiga, Indonesia, with lived experience of suicidal ideation attributed to family factors, were selected via purposive and snowball sampling. Data were collected through in-depth interviews and observations, then analyzed thematically. Eleven key themes emerged: suicidal ideation, suicide attempts, family communication dysfunction, excessive pressure, grief, history of violence, parental overcontrol, responsibility burden, hopelessness, low self-esteem, and protective factors. The findings reveal that suicidal ideation arises from a complex interaction between dysfunctional family dynamics (e.g., poor communication, pressure, violence) and the adolescent's internal psychological state (e.g., hopelessness, low self-esteem). Protective factors, including improved family dynamics, social support, and religiosity, were crucial in mitigating risk. The study underscores the need for early intervention targeting family systems and strengthening protective resources to prevent adolescent suicide. Keywords: suicidal ideation, adolescents, family factors, qualitative study, protective factors